Integrative Network Pharmacology and Transcriptomics Reveal the Mechanism of Gui-Qi-Yi-Shen Granules in the Treatment of IgA Nephropathy - Cao JW; Tang YW; Jiang MY; Lu MD; Yang RC; Yu DR; Wan F (Drug Design, Development and Therapy)
Jia-Wei Cao,1 Yue-Wen Tang,1,2 Meng-Ya Jiang,1 Meng-Dan Lu,3 Ru-Chun Yang,1,4 Dong-Rong Yu,1,4 Feng Wan1,4 1Department of Nephrology, Hangzhou TCM Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China; 2Department of Nephrology, Hangzhou Dingqiao Hospital, Hangzhou, People’s Republic of China; 3College of Life Sciences, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China; 4Zhejiang Key Laboratory of Blood-Stasis-Toxin Syndrome, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of ChinaCorrespondence: Dong-Rong Yu; Feng Wan, Hangzhou TCM Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, 310007, Tiyuchang Road 453, People’s Republic of China, Tel +86-571-88950659, Email yudr68@163.com; wfthebest@163.comBackground: IgA nephropathy (IgAN) is a significant contributor to kidney failure and death, with limited therapeutic options. Gui-qi-yi-shen (GQYS) granules are a classic Chinese medicine prescription for treating IgAN. Nevertheless, the underlying molecular mechanism is still unclear.Purpose: To elucidate the mechanism by which GQYS exerts its therapeutic effects in IgAN treatment.Materials and Methods: Itgam-IRES-hCD89 mice (eight-week-old) were divided into four groups: IgAN, low-dose GQYS (GQYS-L, 5.2 g/kg), high-dose GQYS (GQYS-H, 10.4 g/kg), and Losartan (6.5 mg/kg). Coincident C57/BL6 mice were used as controls. Periodic acid-Schiff (PAS) staining, biochemical analyses, and immunofluorescence (IF) were used for therapeutic evaluation. Network pharmacology and transcriptomic analyses were performed to investigate the potential mechanisms of GQYS, while Western blotting and IF were performed to confirm these actions.Results: Compared to the model group, 24 h proteinuria and alanine aminotransferase levels were significantly reduced in the GQYS groups. PAS staining showed that IgAN mice exhibited glomerular mesangial hypercellularity as well as matrix expansion, whereas these pathologies were alleviated in the GQYS groups. IF results revealed that GQYS reduced deposition of IgA and C3 in the glomerular mesangial areas compared to that in the model mice. Network pharmacology and transcriptomic analyses identified genes and pathways that may be associated with the effects of GQYS against IgAN. Western blotting and IF results indicated GQYS attenuated the expression of TLR4/MyD88/NF-kB and IL-6/JAK2/STAT3 signaling pathway related proteins.Conclusion: GQYS reduced proteinuria and ameliorate renal pathological damage in IgAN via TLR4/MyD88/NF-kB and IL-6/JAK2/STAT3 signaling, offering a promising therapeutic strategy.Keywords: IgA nephropathy, Gui-qi-yi-shen granules, renoprotection, TLR4 signaling pathway, IL-6 signaling pathway